GRATITUDE STRATEGY IN RACHEL GETTING MARRIED MOVIE - Wati, Zurmi; Theresia, Melati; Syafar, Dian Noviani (TELL - US JOURNAL, 2021)
This research is about gratitude strategies in Rachel Getting Married Movie. Gratitude is a word or sentence that someone says when they say thank you to someone else. The purpose of this research is to find the gratitude strategies. It is used Cheng's theory in determining the gratitude strategies that spoken by the main character in  Rachel Getting Married Movie.  This research is a qualitative research. There are three steps that are used in this research, they are collecting data, analyzing data and presenting the result of analyzing. In the collecting data, data were collected by observational method. This method was followed by non-participatory observational, recording and note taking technique. After collecting data, data were analyzed by using identity and distributional method. In addition, the results of data analysis were described by using formal and informal method. In this research, the researchers  found 5 gratitude strategies, they are:thanking, recognition of imposition, apology,other and attention getter.